2012 National Science Foundation Political Science Program Awards. (PS: Political Science & Politics, 2013)
The political science program of the National Science Foundation (NSF) announces its awards for basic research support and dissertation improvement grants for fiscal year 2012. The program funded 68 new projects and 30 doctoral dissertation improvement awards. Additional program funds were spent on continuing grant increments, which result from awards that were made in previous fiscal years, but for which funds are being disbursed on a yearly basis instead of upfront. The program holds two grant competitions annually—Regular Research, August and January 15; and Dissertation Improvement September and January 15—and constitutes a major source of political science research funding as part of fulfilling NSF's mission to encourage theoretically focused empirical investigations aimed at improving the explanation of fundamental social and political processes and structures.